„Der Fliegenpalast“ von Walter Kappacher. Eine Hommage auf Hugo von Hofmannsthal als Auseinandersetzung mit dem „Österreichischen“ - Hackl, Wolfgang (Studia Germanica Posnaniensia, 2019)
In his novel Der Fliegenpalast, Walter Kappacher, an expert on and admirer of Hugo von Hofmannsthal, drew on his profound knowledge of Hofmannsthal’s work, as well as researching extensively on the author and his time. This resulted in a dense fabric of intertextual references to both Hofmannsthal’s work and his reading. Interwoven with this biographical narration is a broad socio-historic panorama of the first decades of the 20th century in Austria. An analysis of the construction of seemingly self-evident Austrian references proves that this novel can only be adequately analyzed and interpreted in the context of Austrian political as well as literary and cultural history.